A Study on the Growth of Venture Capital Financing in India: Exploring Challenges and Opportunities for Entrepreneurs in Venture Capital Financing: A Study in India (Journal of Advances and Scholarly Researches in Allied Education, 2018)
The paper was titled a report on venture capital finance and a survey on founder challenges and opportunities. This paper looks at the challenges and opportunities that entrepreneurs face when it comes to venture capital investing, as well as the worth of venture capital. With 60 respondents, descriptive analysis is conducted using a convenience sampling system. Mean analysis, frequency analysis, independent t measure, ANOVA, and factor analysis were used in the research. Individuals pursuing venture capital can need to change their strategy to various capitalists due to the variety involved, according to the findings. Because of the layout and regulations of capital markets, niches of venture capital remain.